Coping strategies in children between 8 and 12 years old with a diagnosis of learning disorders and a control group of Educational Institutions of the municipality of Garzón, Huila - Zuluaga Arroyave, Tatiana; Gutiérrez Sánchez, Ximena; Zuluaga, Juan Bernardo (Rastros Rostros, 2021)
AbstractObjective: to describe and compare the coping strategies of children diagnosed with a learning disorder be-tween 8 and 12 years old and a control group of Educational Institutions of the municipality of Garzón, Huila, for which a quantitative research method with comparative descriptive scope was used. not experiential. The sample consisted of 40 school children aged between 8 and 12 years, divided into two groups: cases and controls. As information collection instruments, a sociodemographic record and the Coping Scale for Children - EAN (Rodríguez et al., 2012) were used. Results: in the total scores, the highest score in the Problem-Centered Coping style was for the control group with 34.9%; while in the Unproductive Coping style it was for the group of cases, with 35.4%. The comparison between groups showed only a significant difference in the positive attitude strategy, where the control group obtained a score of 10.3% and the case group 9.3%. Conclusions: Children with learning disorders use unproductive coping strategies more frequently, which pre-vents them from understanding necessary skills in social or academic functioning. The neurotypical group frequently uses problem-focused coping strategies, thus achieving a functional understanding of their abilities. The comparison between groups showed only a significant difference in the positive attitude strategy.y.
Keywords: child coping; coping strategies; learning disorders